A Case of Cancer-Associated Hyponatraemia: Primary Adrenal Insufficiency Secondary to Nivolumab - Galliazzo, Silvia; Morando, Filippo; Sartorato, Paola; Bortolin, Michela; De Menis, Ernesto (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Immunotherapy with immune checkpoint inhibitors is a new frontier for cancer treatment. On the safety profile, this drugs class is associated with a new spectrum of side effects, the so-called immune-related adverse events that can potentially affect any organs, mainly endocrine glands. Scant data are available to inform the appropriate strategy of their management and treatment. Case Presentation: A 74-years old man with a squamous non-small cell lung cancer on nivolumab was hospitalized for fatigue, nausea, vomiting and severe hyponatremia. Biochemical tests were significant for hypotonic hyponatremia with a high urine sodium concentration. Endocrine tests showed overt primary hypothyroidism and low serum cortisol and aldosterone levels associated with an elevated circulating level of adrenocorticotrophic hormone. Adrenal antibody screening and the search of adrenal lesion on CT abdomen were negative. Thus, a nivolumab-induced primary adrenal insufficiency was diagnosed. Nivolumab withdrawal and replacement treatment with glucocorticoid and mineralocorticoid allowed clinical and biochemical recovery. Conclusion: Physicians need to be aware of potential immune-related adverse events in all patients treated with an immune checkpoint inhibitor. Their timely recognition is essential to carry out the proper treatment.
Keywords: hyponatraemia